حقوق الإنسان بين عالمية القيم وخصوصية الثقافات وعلاقة ذلك بالعولمة - شعنان, مسعود (revue mofakir, 2018)
Summary  : This study surveys the definition and development of the concept of human rights as well as the controversy that still exists between supporters of the idea of the universality of human rights and those who favor conformity with the specificities of each society. The study also questions the impact of globalization on the acceleration of the universality of human rights. The study tries also to address the double standards and selectivity through which major powers and international organizations handle their evaluation of Arab countries with respect to human rights. In the conclusion, the study makes three future scenarios through which it shows how states , which advocates cultural specifity of rights, maneuvers with international pressures that aim to impose a single global system of human rights. الملخص : هذه الدراسة تتعرض للتعريف والمفهوم والتطور الذي عرفته منظومة حقوق الإنسان ، كما تتناول الجدل الذي لا يزال قائما بين أنصار فكرة عالمية حقوق الإنسان وبين المؤيدين لضرورة ملائمة وانسجام الحقوق مع خصوصيات كل مجتمع . كذلك تتساءل الدراسة عن مدى ظاهرة العولمة على التسريع بعالمية حقوق الإنسان أو الاتجاه نحو عولمتها ’من خلال الدراسة نحاول كذلك التطرق للمعايير المزدوجة والانتقائية التي تتعامل بها الدول الكبرى والمنظمات الدولية تجاه بعض الدول عند تقييمها لمدى احترام هذه الأخيرة لحقوق الإنسان . وفي الأخير تطرح الدراسة ثلاث سيناريوهات مستقبلية نستشف من خلالها كيفية تعامل الدول التي تنادي بالخصوصية مع الضغوطات الدولية التي تريد أن تفرض عليها منظومة عالمية واحدة لحقوق الإنسان .